Lithium-Induced Downbeat Nystagmus and Horizontal Gaze Palsy - Jørgensen, Jesper Skovlund (Open Ophthalmol J, 2016)
We report a case of lithium-induced downbeat nystagmus and horizontal gaze palsy in a 62-year-old woman who was treated for a bipolar affective disorder with lithium carbonate for one month. At presentation serum lithium was within therapeutic range. No alternative causes of the ocular motility disturbances were found, and the patient improved significantly as lithium carbonate was discontinued.